PENGOLAHAN LIMBAH SEKAM PADI MENJADI BIOCHAR UNTUK PEMANFAATAN DAN PENGOLAHAN LIMBAH PADA DESA LATSARI KECAMATAN MOJOWARNO JOMBANG - Afif Ramadhan; Nur Azizah; Kemal Fathirsyam; Roziana Febrianita (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Biobriquettes are solid alternative fuels in the form of biochar made from carbon materials, with high calorific value content and long combustion power. This activity was c arried out by a group of students who adjusted the production process to field problems, including socialization and training in making charcoal briquettes from rice husks in Latsari Village, Mojowarno District, Jombang Regency. The researcher carried out direct observation in Latsari Village to understand the situation and problems they faced, especially in the field of rice fields. Biobriquettes made from organic waste with additional adhesives offer a more sustainable and economical alternative to firewood. The introduction and training program activities for making charcoal briquettes from rice husks were successfully carried out in Latsari village in line with the plans and targets that have been set. Through this activity, rural communities can utilize rice husk waste to produce products that not only reduce pollution but also increase income.